KLINIK HUKUM FORMIL DALAM PERKAWINAN - Tumian Lian D. Purba; Tri Yanuaria (JURNAL PENGABDIAN PAPUA, 2020)
PKM Law clinic formil in a marriage performed for the Distrik Sentani Timur on their Kampung Asei Kecil and Kampung Harapan Nolokla. Basically the province of Papua are still abnormally low level of community knowledge about the implementation of lawful matrimony according to the law number 1 of 1974 about the marriages. District of Sentani Timur still have higher rates of domestic violence is a to alamoth probably the treble because of the limited the knowledge of a community in protect of the rights. Peoples insight to which most of the work as farmers and fishermen .The people living in village’s Asei Kecil and village’s Harapan Nolokla a lot of do not know a result of not marriages between the single last year, so that an increasing number of households the proportion who experienced violence especially was happening in the wife who escorted them on. A virtuous and worthy wife do not have a marriage certificate will be more will be done to anyone in the law of national. Method in the implementation of the PKM this by means of talk and discussions with the purpose of open peoples insight about the importance of registration marriage, technical training and assistance directly involving an advocate, population and civil last, the board the customs and religious leaders local. The outer covering of PKM this is increase the amount of community awareness of the importance of the implementation of lawful matrimony according to legislative regulations, and the issuance of the marriage certificate, other the population documents namely family card, an identity card. Birth certificate from the community who are married as a condition the issuance of the marriage certificate. Keywords: Clinic, Formil Law, Marriage, law